Cobalt-Phosphate modified TiO2/BiVO4 nanoarrays photoanode for efficient water splitting. (23rd February 2017) - Tong, Rui; Wang, Xina; Zhou, Xiaolong; Liu, Qingyun; Wang, Hanbin; Peng, Xiaoniu; Liu, Xiang; Zhang, Zhihua; Wang, Hao; Lund, Peter D.
Abstract: Using TiO2 nanorods as one-dimensional (1D) electron transport tunnel, BiVO4 as light harvester, and Co-Pi (Cobalt-Phosphate) as co-catalyst, TiO2 /BiVO4 /Co-Pi nanorod arrays were fabricated as efficient photoanode on a FTO substrate for photoelectrochemical (PEC) water splitting cells. It was found that the monoclinic BiVO4 nanoflakes were mainly vertically attached to the side faces of rutile TiO2 nanorods with an average size of ∼35 nm and a selective growth direction along <112>. By changing the electrodeposited quantity of BiVO4, the effect of the loading density of BiVO4 on the PEC performance was systematically studied, and an optimum photocurrent of ∼1.86 mA cm −2 at 1.0 VRHE with an onset potential as small as 0.3 VRHE and IPCE of 26% (at 450 nm) was obtained for the TiO2 /BiVO4 /Co-Pi anodes. Electrochemical impedance spectroscopy showed that Co-Pi can greatly decrease the charge transfer resistance at the photoanode/electrolyte interface. Along with the band alignment of the 1D nanoarray heterostructure beneficial for the charge separation, a hydrogen production of ∼7.31 μmol cm −2  h −1 was achieved for the efficient water splitting system. Such a heterostructured 1D nanoarray configuration can be extended to other PEC water splitting systems as well to increase the number of reactive sites and absorption of solar light, and to enhance the OER kinetics. Graphical abstract: Highlights: TiO2 /BiVO4 /Co-Pi nanorod arrays were fabricated as efficient photoanodes for photoelectrochemical water splitting cells with a photocurrent density of ∼1.86 mA/cm 2 at 1.0 VRHE . Further reduction in interface transfer resistance was found after modified by Co-Pi. The charge separation and transfer mechanism were demonstrated along with the band alignment and oxygen evolution kinetics.